Review of the new electronic technologies and analysis of the development of modern bank - Нєізвєстна, Олена Володимирівна (Technology audit and production reserves, 2016)
The aim of the article is reviewing the prospects for physical functioning of the banks and their capacity to provide banking services in light of the strong financial development of new electronic technologies and increased competition from non-bank institutions. Analyzing, summarizing and systematizing research work of many scientists it is discovered the relationship between the rapid development of computer and telecommunications technology and efficiency of both the banking and channels of sales, market expansion and geography of services using by the client. Studying conditions and possibility of introducing modern computer technology in the practice of banks Ukraine it is represented the author's position on further technological development of Internet banking in Ukraine in two main ways: first, by expanding the functionality of existing proposals, implementation of advanced services; and secondly, through the development of new interface platforms. It is proved that the banks those are a powerful interface platform and have open API and offer the best product solutions and mobile applications is the most competitive and have prospects for existing in the coming years. It is proposed using Big Data technology, which allows to remotely managing the relationship of the banks with customers through mass personalization.